Overspecification of color, pattern, and size: salience, absoluteness, and consistency - Tarenskeen, Sammie; Broersma, Mirjam; Geurts, Bart (Frontiers in Psychology, 2015)
The rates of overspecification of colour, pattern, and size are compared, to investigate how salience and absoluteness contribute to the production of overspecification. Colour and pattern are absolute attributes, whereas size is relative and less salient. Additionally, a tendency towards consistent responses is assessed. Using a within-participants design, we find similar rates of colour and pattern overspecification, which are both higher than the rate of size overspecification. Using a between-participants design, however, we find similar rates of pattern and size overspecification, which are both lower than the rate of colour overspecification. This indicates that although many speakers are more likely to include colour than pattern (probably because colour is more salient), they may also treat pattern like colour due to a tendency towards consistency. We find no increase in size overspecification when the salience of size is increased, suggesting that speakers are more likely to include absolute than relative attributes. However, we do find an increase in size overspecification when mentioning the attributes is triggered, which again shows that speakers tend refer in a consistent manner, and that there are circumstances in which even size overspecification is frequently produced.